DINAMIKA PARTISIPASI POLITIK NINIK MAMAK NAGARI MAUARA PANAS DALAM PILKADA SERENTAK KABUPATEN SOLOK TAHUN 2015 - Ardila, Nelta; Erviantono, Tedi; Noak, Piers Andreas (Jurnal Nawala Politika; 2017, 2017)
The rulers of Minangkabau are inseparable from the leader of the tribe or clan, named Ninik Mamak. Ninik Mamak has responsibility for the tribe that he leads. As a framing, author using social capital theory which wants to know the strength of the network in a particular group. In this study the strength of Ninik Mamak network and its related tribal equations. The method used in this research is qualitative research method by using ethnography approach. The findings of research that the authors get in the field related to the existence of ninik mamak in Nagari Muara Panas on the elections simultaneously in Solok District in 2015 found that the people of Nagari Muara Panas still recognize the existence of ninik mamak in the middle of society and still believe in the words ninik mamak this Proven in terms of tradition and also the political aspect.   Keywords: Network, Clan, NinikMamak, Elections.